Influence of Internet accessibility and demographic factors on utilization of web-based health information resources by resident doctors in Nigeria (2014)
The internet is a huge library with avalanche of information resources including healthcare information. There are numerous studies on use of electronic resources by healthcare providers including medical practitioners however, there is a dearth of information on the patterns of use of web-based health information resource by resident doctors. This study therefore investigates the influence of internet accessibility and demographic factors on utilization of web-based health information resources by resident doctors in tertiary healthcare institutions in Nigeria. Descriptive survey design was adopted for this study. The population of study consist of medical doctors undergoing residency training in 13 tertiary healthcare institutions in South-West Nigeria. The tertiary healthcare institutions are Federal Medical Centres, University Teaching Hospitals and Specialist Hospitals (Neuropsychiatric and Orthopaedic). A pretested, self-administered questionnaire was used for data collection. The Statistical Package for the Social Sciences (SPSS) was used for data analysis. Data were analyzed using descriptive statistics, Pearson Product Moment correlation and multiple regression analysis. The mean age of the respondents was 34 years and males were in the majority (69.0%). A total of 96.1% respondents had access to the Internet. E-mail (x=5.40, SD=0.91), Google ( =5.26, SD=1.38), Yahoo (2 =5.15, SD=4.44) were used weekly by the respondents. Preparation for Seminar/Grand Round presentation ( 2 =8.4, SD=1.92), research ( =7.8, SD=2.70) and communication (2 =7.6, SD=2.60) were ranked high as purposes for use of web-based information resources. There is a strong, positive and significant relationship between internet accessibility and utilization of web-based health information resources (r=0.628, p<0.05). Internet accessibility (B=0.911) and demographic variables: gender B=-2.027), designation (B=-0.343) educational qualification (B=2.4 1 1) significantly influence utilisation of web-based health information resources of the respondents. A great majority of the respondents have access to the Internet and used web-based health information resources more for academic purposes than patient care. Training is required to promote use of internet health information resources among resident doctors. The findings of this study will be useful to the management of the 13 healthcare institutions regarding provision of appropriate internet facilities that will enhance access and use of web-based health information resources by resident doctors.